Building Salted Egg MSMEs on the Basis of Spiritual Value - Azka Nafis Dhukaya; Faradela Nurul Aulia; Rosalina Rosyidina; Moh. Akram Farras Fajari; Ngizzul Muhtraom; Muhammad Gusta Adi Nugraha; Muhammad Riyan Pradana; Zidny Nabiel Hussein (Universitas Kristen Indonesia Toraja, 2024)
This qualitative research aims to explore how spiritual values can be a differentiator between salted egg MSMEs and competitors, so as to attract greater consumer interest. The research is motivated by the business potential in the food sector in Indonesia, with a focus on micro, small and medium enterprises (MSMEs) in the production and marketing of salted eggs. The purpose of this research is to provide an in-depth understanding of how spiritual value can help MSMEs that are being run and with these values can make the business a benefit as well as a blessing.